APLIKASI ASISTEN UNTUK LANSIA DENGAN MEMANFAATKAN SMARTPHONE BERBASIS ANDROID - Purna Sastriya, Gede Edy; Khrisne, Duman Care; Made Surdarma (LPPM STMIK STIKOM Indonesia, 2019)
This study aims to design and build an android based elderly assistant application  using Android Studio Software to help the elderly in performing its activities. There are two features in this elderly assistant application that are Exercise feature and Map Feature. Exercise feature aims to assist elderly in exercising by utilizing accelerometer and gyroscope sensors to read and calculate exercise movement performed by elderly and the Map feature aims to track the location where the elderly are snd also receive the notification when the elderly out of radius. From the results of trials of elderly assistant applications, accelerometer and gyroscope sensors on exercise features have been able to calculate and read the exercise movement that performed by the elderly and the map feature have been able to track the elderly location using GPS on Smartphone.